Dissemination of Information on Neutropenic Diet by Top US Cancer Centers: In-line with the Evidence?. (17th November 2019) - Brown, Timothy J.; Mukhija, Dhruvika; Premnath, Naveen; Venkatraman, Anand; Jiv Singh Nagpal, Sajan; Gupta, Arjun
Abstract: Aim: The neutropenic diet is commonly prescribed to cancer patients with neutropenia with the goal of reducing infections. However, multiple randomized trials have proved no benefit with neutropenic diets compared to less restricted diets with regards to reducing infectious risk. We aimed to ascertain if top cancer centers recommended for or against the use of neutropenic diets on their official websites. Methods: We reviewed the websites of the top 20 hospitals in the 2017 US News Best Hospitals for Cancer©, and ascertained recommendations for neutropenic diet (for, against, equivocal, or not addressed). Results: Seven websites (35%) made recommendations for, four (20%) against, and nine (45%) did not address the neutropenic diet. Only five (25%) backed any of their recommendations with evidence (four against, one for), including two (10%) links to abstracts (both against), whereas seven mentioned the FDA safe food handling guidelines (non-exclusive). Type of recommendation made (for or against) did not depend on US News rank (top vs bottom 10; p = 1.00.). Conclusion: The neutropenic diet continues to be recommended on many (35%) websites of top US cancer centers, despite strong evidence against its use. The website content of major US cancer centers should be updated to better guide patients regarding neutropenic diets.